Hubungan Antara Computer Self-Efficacy dan Kecemasan Menggunakan Komputer - Musfirah Musfirah; Ratna Syifa’a Rahmahana; Retno Kumolohadi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2003)
This research is aimed at describing the relationship between computer self-efficacy and computer anxiety. The hypothesis of this research was there are the negative relationships between computer self-efficacy and computer anxiety.The partisipants of this reserch were 86 students. The sample consisted of 38 males and 48 females, have graduated from senior high school and aged 18-30 years at one of Computer Education Course in Yogyakarta. Participants were asked to complete the 43-item of computer self-efficacy scale and 46-item of computer anxiety scale. The result showed that computer self-efficacy was be a very negatively significant related to computer anxiety (r= -0,777 ; p= 0,00 – 0,001). The data of this research were analized with product moment from Pearson in SPSS vertion 11,00. The contribution (R-squared) of computer self-efficacy in reducing computer anxiety was 60,4%.Kata kunci: Computer Self-Efficacy, Kecemasan Menggunakan Komputer